2000
DOI: 10.1111/0002-9092.00091
|View full text |Cite
|
Sign up to set email alerts
|

Financial Structure of Farm Businesses under Imperfect Capital Markets

Abstract: Recent finance studies have considered whether gaps between a firm's costs of internal and external sources of investment funds, arising from capital market imperfections, influence its investment behavior and funding preferences. This study tests the applicability of the pecking order and partial adjustment theories of financial structure to farm businesses by fitting a set of simultaneous financial equations with farm panel data from Illinois. Model results indicate that Illinois farms adjust to long-run fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 26 publications
4
52
0
7
Order By: Relevance
“…One possible explanation is that there are significant increasing returns to scale in agricultural production and that government payments-which provide cash and perhaps also increase leverage for loansrelieve borrowing constraints and allow some farms to transition more quickly to an efficient scale. This explanation would be consistent with studies finding increasing returns to scale (e.g., Morrison Paul et al 2004;Morrison Paul and Nehring 2005) and liquidity constraints in agriculture (e.g., Hubbard and Kashyap 1992;Bierlen and Featherstone 1998;Barry, Bierlen, and Sotomayor 2000;Roberts and Key 2002).…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation is that there are significant increasing returns to scale in agricultural production and that government payments-which provide cash and perhaps also increase leverage for loansrelieve borrowing constraints and allow some farms to transition more quickly to an efficient scale. This explanation would be consistent with studies finding increasing returns to scale (e.g., Morrison Paul et al 2004;Morrison Paul and Nehring 2005) and liquidity constraints in agriculture (e.g., Hubbard and Kashyap 1992;Bierlen and Featherstone 1998;Barry, Bierlen, and Sotomayor 2000;Roberts and Key 2002).…”
Section: Discussionsupporting
confidence: 89%
“…The tax shield effect has an influence on the choice of financing sources and, therefore, on the weighted average cost of capital (Barry et al 2000). Farms in Poland do not pay income tax, 2 as they are subject to agricultural tax charged on the basis of the arable land area and location within a specified tax region (Wasilewski et al 2016).…”
Section: Understanding the Cost Of Capitalmentioning
confidence: 99%
“…Financial characteristics Previous studies found that cash flow was a significant determinant of machinery investment (Barry et al, 2000;Bierlen and Featherstone, 1998). Cash flow is typically used as a proxy for investment opportunity using net present value as a base for calculating cash flows.…”
Section: Impact Of the Section 179 Tax Deductionmentioning
confidence: 99%